Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.20435/pssa.v10i3.695
|View full text |Cite
|
Sign up to set email alerts
|

Violência contra mulher no namoro: percepções de jovens universitários

Abstract: A atenção pré-natal consiste no acolhimento à mulher desde os primórdios da gestação. O objetivo deste estudo foi compreender a vivência do acompanhamento pré-natal na perspectiva de mulheres assistidas pelo Sistema Único de Saúde (SUS). Foram entrevistadas 11 mulheres, residentes no município de Uberlândia, Minas Gerais, em 2015. Foi utilizado um roteiro de entrevista semiestruturado composto por: (a) dados de caracterização da participante; e (b) questões norteadoras para investigar o transcorrer da gestação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
0
3
0
8
Order By: Relevance
“…27 In the academic trajectory, university students identified as violent those behaviors that caused visible or physical damage, referring to corporal violence as the most recognized, moral and psychological violence against women were the most present in the courtship among respondents, followed by sexual, physical and patrimonial. 28 These results highlight the importance of including gender equality debates with respect to the limits established in interpersonal relations.…”
Section: Discussionmentioning
confidence: 96%
“…27 In the academic trajectory, university students identified as violent those behaviors that caused visible or physical damage, referring to corporal violence as the most recognized, moral and psychological violence against women were the most present in the courtship among respondents, followed by sexual, physical and patrimonial. 28 These results highlight the importance of including gender equality debates with respect to the limits established in interpersonal relations.…”
Section: Discussionmentioning
confidence: 96%
“…They pointed the occurrence of psychological (46.8%), sexual (40.4%), moral (31.9%), physical (8.5%), and patrimonial (2.1%) violence. By mentioning psychological violence as being the type most practiced in sexual-emotional relationships, they highlighted masculinity, power, and guarantees of authority in this type of relationship, and indicated that they see this form of violence as an instrument for solving conflicts (13) .…”
Section: Resultsmentioning
confidence: 99%
“…It is understood that MCPs are important tools for understanding and coping with violence against and between young university students, and that they allow contextualization of the increase of various types of violence in Brazilian universities. Ideas about the existence of faith that education can create a civilized and pacifist society, and of making personal resources available to cope with violence, are common sense beliefs, but frequent complaints of discrimination and violent acts in the university setting expose another reality (12)(13) . In this context, it is understood that MCPs allow contextualization of the increase of violence in Brazilian public universities and, consequently, helping to understanding and to cope with this phenomenon in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Normalmente atos mais agressivos são facilmente identificados como violências. Porém comportamentos como perseguição e manipulação são menos reconhecidos, o que pode contribuir para que muitas mulheres não percebam que estão dentro de uma relação abusiva (Souza, Pascoaleto, & Mendonça, 2018).…”
Section: Violência Nas Relações Afetivasunclassified